Bayesian Claims Reserving Methods in Non-life Insurance with Stan An Introduction - Gao, Guangyuan (Springer Singapore, 2018)
This book first provides a review of various aspects of Bayesian statistics. It then investigates three types of claims reserving models in the Bayesian framework: chain ladder models, basis expansion models involving a tail factor, and multivariate copula models. For the Bayesian inferential methods, this book largely relies on Stan, a specialized software environment which applies Hamiltonian Monte Carlo method and variational Bayes. .